Injury Prevention Programmes in Male Soccer Players: An Umbrella Review of Systematic Reviews - Joel Barrera; Antonio J. Figueiredo; Filipe Manuel Clemente; Adam Field; Luis Valenzuela; Hugo Sarmento (Journal of Men's Health, 2022)
Background: The incidence of lower-extremity injuries in soccer is high, with effective injury prevention programmes shown to reduce injury rates. Over the past decades, an exponential growth has occurred in the number of scientific publications including review articles on injury prevention programmes in male soccer. Accordingly, it is timely to summarise findings from potential systematic reviews and meta-analyses in the form of an umbrella review. Objective: This umbrella review was conducted to review, synthesise and appraise the findings of the published systematic reviews and meta-analyses that investigated the effects of injury prevention programs in male soccer players. Methods: Following pre-registration on the International Platform of Registered Systematic Review and Meta-analysis Protocols (https://inplasy.com/inplasy-2021-9-0066/) and according to PRISMA guidelines, a search of databases (Web of Science, Scopus, SPORTDiscus and PubMed) was conducted for studies published before June 2021. Studies were eligible if they included male (amateur to professional) soccer players, included studies that incorporated injury prevention programs with a control and intervention group(s), and adopted the form of a systematic review (with or without a meta-analysis). The methodological quality of the evidence was assessed using the AMSTAR 2 tool. Results: Eight systematic reviews (no meta-analyses) were included in the umbrella review. The review articles retained for analyses primarily focused on the prevention of injuries in the lower limbs, with primary focus on the hamstrings. Prevention programs principally incorporating strengthening, proprioception and multi-component protocols (balance, core stability, functional strength and mobility) revealed positive effects on injury incidence and severity. Implementing eccentric hamstring protocols demonstrated efficacy in decreasing hamstring injury and proprioception exercises reduced the risk of ankle sprains. It was also revealed that dynamic warm-ups were effective in reducing incidence, but not severity of injuries. Conversely, the evidence from the current umbrella review suggests that programs focusing on static stretching showed inconclusive injury preventative effects. Articles were of mixed methodological quality with one demonstrating high quality, two indicating low quality and five were of critically low quality. Conclusions: The systematic reviews in this area suggests that prevention programs developing muscle strength and proprioception are effective in reducing the incidence and severity of injury (time out). Dynamic movements performed before a match are effective in reducing injury incidence, whilst the effects of warm-ups incorporating static stretching are unclear. Future original studies on this topic with improved methodological quality and consistency among experimental study designs should be conducted to evaluate the benefits of different programs over longer periods in male soccer players.